Electrosynthesis and study of some physical properties of conductive and solid-state gas sensing polydiphenylamine - YUMAK YAHŞİ, AYŞE (ELSEVIER SCIENCE SA, 2015)
Polydiphenylamine was prepared using electrochemical oxidation of the corresponding monomer diphenylamine in an acetonitrile solution containing sodium perchlorate (NaClO4) and characterized spectroscopically. First, some physical characterization using infrared (FTIR) measurement shows that this material has a polymeric structure. Moreover, Differential Scanning Calorimetry (DSC) and thermal gravimetric analysis (TAG) showed a good stability at temperatures above 200 degrees C. Second, the electrical conductivity and dielectric properties of polydiphenylamine were studied as guides for sensing performance using impedance spectroscopy technique in the frequency range 5 Hz-13 MHz at various temperatures (118-150 degrees C). DC conductivity is thermally activated with activation energy around 0.65 eV. On the other hand AC conductivity is investigated through Jonscher law. The imaginary part of the complex impedance has a maximum whose relaxation frequency increases with temperature according to Arrhenius law. Finally, Values of dielectric constants epsilon(1) and epsilon(2) were calculated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Polydiphenylamine; Electro polymerization; FTIR; Impedance spectroscopy; ELECTRON-TRANSFER; THIN-FILMS; POLY(DIPHENYLAMINE); AMINODIPHENYLAMINE; COMPOSITE; OXIDATION; POLYMER; CELLS